Trophic transfer and effects of DDT in male hornyhead turbot (Pleuronichthys verticalis) from Palos Verdes Superfund site, CA (USA) and comparisons to field monitoring - Crago, Jordan (Environ Pollut, 2016)
High concentrations of DDT and metabolites (ΣDDT) have been detected in sediment and the demersal flatfish hornyhead turbot (Pleuronichtys verticalis) collected from Palos Verdes (PV), California, USA, a site contaminated with over 100 metric tons of DDT throughout 1960s to 70s. This study was elaborated to assess the transfer of ΣDDT from PV-sediment into polychaete (Neanthes arenaceodentata) and hornyhead turbot, and to investigate if the genomic responses in turbots from two different laboratory exposures mimic those in turbots caught in PV (PV-turbot). Turbot fed PV-sediment-contaminated polychaete for 7 days had liver concentrations of ΣDDT similar to PV-turbot. After 28 days, ΣDDT also accumulated by livers of turbot gavaged with ΣDDT mixture. In vitro cell bioassays indicated significant increases of 17β-estradiol equivalents (EEQ) in turbots as compared to the control in the 7-day study. These responses corresponded to those measured in PV-fish. Glucocorticoid receptor (GR), anti-androgen receptor (anti-AR), estrogen receptor (ER) or aryl hydrocarbon receptor (AhR) activities were also observed in PV-sediment, and PV-sediment-exposed worm. Anti-AR, AhR and GR activities were significantly higher in PV-sediment than reference sediment (San Diego, SD). Higher transcripts of hepatic VTG, ERα and ERβ were found in PV-turbot than SD-turbot, but unaltered in fish exposed to sediment-contaminated worms for the 7-day study. In contrast, liver extracts from the 28-day treatment of ΣDDT showed lower EEQ but similar hepatic VTG and ERβ transcripts relative to those of PV-turbot. These data indicated that trophic transfer of sediment-associated DDT in 7-day exposures corresponded to field measurements of DDT residues and in vitro ER bioactivities, but failed to mimic in vivo biological effects observed in field fish. In contrast, treatment with ΣDDT alone for 28 days mimicked in vivo biological effects of DDTs in PV fish, but did not correspond to liver concentrations or in vitro bioactivities.